EXTERNAL STATE ECONOMIC DEBT - Norbaev Tura (Scholars Digest Publishing, 2024)
The article examines the impact of the level of external debt of the state on its economy and global financial stability. The authors consider the main causes of foreign debt, its consequences for the national currency, financial markets and international relations. The article also analyzes strategies for managing external debt, measures to reduce its level and possible risks associated with excessively high debt obligations. Let's also look at the statistics of countries with external debts.
Keywords: external debt, credit, loans, financial stability, economy.